An East Asian subgroup analysis of PROCLAIM, a phase III trial of pemetrexed and cisplatin or etoposide and cisplatin plus thoracic radiation therapy followed by consolidation chemotherapy in locally advanced nonsquamous non–small cell lung cancer. Issue 4 (17th June 2016) - Wang, Luhua; Wu, Yi‐Long; Lu, Shun; Deng, Lei; Ahn, Myung‐Ju; Hsu, Feng‐Ming; Iscoe, Neill; Hossain, Anwar; Puri, Tarun; Zhang, Pinghai; Orlando, Mauro
Abstract: Aim: PROCLAIM, a phase III trial of patients with nonsquamous non–small cell lung cancer comparing concurrent pemetrexed‐cisplatin and thoracic radiation therapy followed by consolidation pemetrexed, did not meet its primary endpoint of superior overall survival versus etoposide‐cisplatin and thoracic radiation therapy followed by a consolidation platinum doublet of choice. The results from an East Asian subgroup analysis are presented here. Methods: A subgroup analysis was performed for all patients randomized from China ( n = 61), Taiwan ( n = 25), and Korea ( n = 11). Results: Baseline characteristics were balanced between treatment arms for East Asian patients. In the 97 randomized East Asian patients, median overall survival was 26.8 months for the pemetrexed‐cisplatin arm and 36.3 months for the etoposide‐cisplatin arm (hazard ratio: 1.23; 95% confidence interval: 0.70–2.14; P = 0.469). Median progression‐free survival was 10.0 months for the pemetrexed‐cisplatin arm and 7.6 months for the etoposide‐cisplatin arm (hazard ratio: 0.97; 95% confidence interval: 0.61–1.54; P = 0.890). The objective response rate was 47.7% in the pemetrexed‐cisplatin arm and 34.0% in the etoposide‐cisplatin arm ( P = 0.167). In the 90 treated East Asian patients, the overall incidence of drug‐related grade 3–4 treatment‐emergent adverse events was significantly lower in the pemetrexed‐cisplatin arm versus the etoposide‐cisplatin arm (61.4% vs 91.3%; P = 0.001). Conclusion: For East Asian patients, pemetrexed‐cisplatin combined with thoracic radiation therapy, followed by consolidation pemetrexed, did not improve overall survival but did have a good safety profile with a trend for improved progression‐free survival and objective response rate compared to standard chemoradiotherapy for stage III unresectable nonsquamous non–small cell lung cancer.